2017
DOI: 10.1128/jb.00297-17
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Microbial Cooperation Mediated by Public Goods in Single- and Multiple-Trait Scenarios

Abstract: Microbes often form densely populated communities, which favor competitive and cooperative interactions. Cooperation among bacteria often occurs through the production of metabolically costly molecules produced by certain individuals that become available to other neighboring individuals, called public goods. This type of cooperation is susceptible to exploitation, since non-producers of a public good can benefit from it while saving the cost of its production (cheating), gaining a fitness advantage over produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 125 publications
0
95
0
Order By: Relevance
“…); in microorganisms, each trait could be the production of a specific amino acid that is released into the external environment from which it can then be absorbed and used by group members (e.g., Özkaya et al. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…); in microorganisms, each trait could be the production of a specific amino acid that is released into the external environment from which it can then be absorbed and used by group members (e.g., Özkaya et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…We model the coevolution of two nonnegative quantitative traits, labeled 1 and 2, that each capture participation to a different public good. For example, in group living mammals, one trait could be the time/energy invested into foraging for the group's offspring, and the other, investment into defending the group by standing sentry against predators (e.g., Carter et al 2014); in microorganisms, each trait could be the production of a specific amino acid that is released into the external environment from which it can then be absorbed and used by group members (e.g., Ozkaya et al 2017).…”
Section: Two Public Goods Modelmentioning
confidence: 99%
“…; Bruger and Waters ; Özkaya et al. ). Here, we studied siderophore production in B. cenocepacia H111 and found that patterns of siderophore sharing and exploitation can be very different from the ones reported for P. aeruginosa .…”
Section: Discussionmentioning
confidence: 99%
“…; Özkaya et al. ). A large body of work has tackled this question and revealed that cheating and cheater control are major determinants of bacterial population dynamics in host infections, in laboratory experiments, and in environmental communities (Cordero et al.…”
mentioning
confidence: 95%
“…Another pair of traits whose evolution is likely to be influenced by their joint expression in different individuals is the production and exploitation of a public good, such as the secretion and use of siderophores by microorganisms (West et al, 2006). Under limited diffusion of siderophores and limited bacterial dispersal (Nadell et al, 2009, Kümmerli et al, 2014, Ross-Gillespie et al, 2015, we expect kin selection effects to be ecologically relevant for how secretion and use of siderophores are associated, and more generally for patterns of multi-trait social variation within microbial communities (Cordero and Polz, 2014, van Gestel et al, 2015, Özkaya et al, 2017, Schiessl et al, 2019, Rodríguez Amor and Dal Bello, 2019.…”
Section: Discussionmentioning
confidence: 99%